ENHANCING ACCUMULATION OF OMEGA 3 AND 9 FATTY ACIDS IN CHLORELLA VULGARIS UNDER MIXOTROPHIC NUTRITION - E. EL-Mohsnawy; M. M. El-Sheekh; M. E.M. Mabrouk; W. F. Zohir (Journal of Animal and Plant Sciences, 2020)
Omega fatty acids have critical part in enhancing general health and protection against serious diseases. The present work showed the distinctive nutritional regimes on Chlorella vulgaris which resulted in switch of metabolic pathways that not only prompted the dry weight and lipid yield, but also upgraded the yield of special fatty acids, omega 3 and 9 fatty acids, which consequently improved the food quality for human and aqua-creatures. High biomass and lipid production were accomplished by either cultivating C. vulgaris at low nitrogen content medium and/or mixotrophic nutrition by glycerol or sugarcane molasses. Glycerol supplementation promoted the dry weight achieving 171% at 0.1 M and 185% at 0.2 M, while the highest total lipid yield (179%) recorded at 0.1 M. GC–MS qualitative and quantitative analysis showed the high yield of α-Linolenic acid to 281%, Eicosapentaenoic acid to 207% at glycerol (0.1 M). Elaidic acid (C18:1t ω9) enhanced almost 14 times, while Erucic acid (C22:1 ω9) enhanced to 256% under glycerol supplementation to growth medium.
Keywords: Chlorella vulgaris; Omega 3; 9; mixotroph; fatty acids; gas chromatography